Dust clouds, climate change and coins: consiliences of palaeoclimate and economy in the Late Antique southern Levant. (4th May 2017) - Fuks, D.; Ackermann, O.; Ayalon, A.; Bar-Matthews, M.; Bar-Oz, G.; Levi, Y.; Maeir, A. M.; Weiss, E.; Zilberman, T.; Safrai, Z.
Abstract : The climate factor has become a focus of much historical and archaeological investigation, encouraged recently by improvements in palaeoclimatic techniques and interest in global climate change. This article examines correlations between climate and history in the Byzantine southern Levant ( c. 4th–7th centuries AD). A proposed 5th century economic downturn attested to by numismatic trends is shown to coincide with palaeoclimatic evidence for drought. We suggest a climatic ultimate cause for the apparent economic decline. In addition, the relationship between the Dust Veil Index (DVI) and annual precipitation in Jerusalem suggests the likelihood of increased precipitation following the 536 AD volcanic dust veil. This prediction is borne out by high-resolution precipitation reconstructions from Soreq Cave speleothems and by sedimentation records of extreme flash flooding. These finds complement palaeoclimatic reconstructions from Europe showing a drop in precipitation after 536 AD. Drought in Europe and flooding in the Middle East are both expected outcomes of global cooling during volcanic winters, such as those described in historical accounts of the 530s AD.